Surgical and Radiologic Anatomy - Duparc, Fabrice; SpringerLink (Online service) (Paris : Springer Paris : Imprint: Springer.)
Anatomy is a morphological science which cannot fail to interest the clinician. The practical application of anatomical research to clinical problems necessitates special adaptation and selectivity in choosing from numerous international works. Although there is a tendency to believe that meaningful advances in anatomy are unlikely, constant revision is necessary. Surgical and Radiologic Anatomy, the first international journal of Clinical anatomy has been created in this spirit. Its goal is to serve clinicians, regardless of speciality-physicians, surgeons, radiologists or other specialists-as an indispensable aid with which they can improve their knowledge of anatomy. Each issue includes: Original papers, review articles, articles on the anatomical bases of medical, surgical and radiological techniques, articles of normal radiologic anatomy, brief reviews of anatomical publications of clinical interest. Particular attention is given to high quality illustrations, which are indispensable for a better understanding of anatomical problems. Surgical and Radiologic Anatomy is a journal written by anatomists for clinicians with a special interest in anatomy.
Keywords: Human anatomy; Radiology; Orthopedics; Surgery; Imaging / Radiology; Surgery; Anatomy; Orthopedics